Antonin Ladinsky’s Poem “The Argonauts”: Reception of a Myth and Literary Symbols - Chevtaev, Arkadyi (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The article deals with the poetics of Antonin Ladinsky’s under-researched poem “Argonavty” (“The Argonauts”, 1926), which represents the author’s interpretation of the ancient myth. The analysis of this poetic text shows that the emphatic combination of elements of ancient reality and Russian reality turns the depicted “Argonautic voyage” into a symbolic ascent to the spiritual heights of the universe. The artistic symbolism, which determines the logic of the narrative development in the poem, explicates the opposition between life and death in their axiological unity and produces the ideologeme of the transfiguration of being. The conclusion is that the “Argonautic” myth in the poem is associated with the poet’s enquiry in the sphere of ontology and philosophy of history; it postulates the need to achieve not only the ideal (the “golden fleece”), but also the awareness of its axiological essence.